2018
DOI: 10.1590/2175-7860201869229
|View full text |Cite
|
Sign up to set email alerts
|

Flora do Ceará, Brasil: Polygalaceae

Abstract: ResumoO objetivo deste trabalho foi realizar o levantamento florístico dos representantes de Polygalaceae, como parte do projeto Flora do Ceará. O estudo foi baseado na análise de caracteres morfológicos de espécimes obtidos em campo e em coleções dos herbários EAC, BHCB, HST, HVASF, RB e UFP. As excursões ao campo foram realizadas no período de setembro/2015 a março/2016. As identificações foram feitas com o auxílio de bibliografias especializadas, confirmadas pela análise de coleções-tipo. Para o estado do C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…In addition, it is worth noting that the number of species indicated for the flora of Ceará (BFG 2018; Flora do Brasil 2020 under construction) is incomplete. Recent studies linked to the "Flora of Ceará Project: knowing to conserve" have shown how much the floristic diversity of that state is underestimated, confirmed with quotes from new records (Capistrano & Loiola 2015;Tabosa et al 2016;Rocha et al 2018;Lima et al 2018Lima et al , 2020Sampaio et al 2019a) or description of new species (Loiola 2013;Souza et al 2016;Sampaio et al 2016Sampaio et al , 2019bRibeiro et al 2017).…”
Section: Introdutionmentioning
confidence: 86%
“…In addition, it is worth noting that the number of species indicated for the flora of Ceará (BFG 2018; Flora do Brasil 2020 under construction) is incomplete. Recent studies linked to the "Flora of Ceará Project: knowing to conserve" have shown how much the floristic diversity of that state is underestimated, confirmed with quotes from new records (Capistrano & Loiola 2015;Tabosa et al 2016;Rocha et al 2018;Lima et al 2018Lima et al , 2020Sampaio et al 2019a) or description of new species (Loiola 2013;Souza et al 2016;Sampaio et al 2016Sampaio et al , 2019bRibeiro et al 2017).…”
Section: Introdutionmentioning
confidence: 86%
“…As espécies de Polygalaceae são utilizadas tradicionalmente em todo o mundo e são grandes representantes destes espécimes pouco explorados pela ciência (GIRALDI;HANAZAKI, 2010). Com distribuição cosmopolita, elas compreendem 19 gêneros e aproximadamente 1300 espécies, tendo 11 gêneros e 199 espécies descritas no Brasil na qual 123 são endêmicas (LIMA et al 2018).…”
Section: Introductionunclassified